Isolation and identification of pathogenic bacteria from red tilapia in cage-cultured system and its environment - Gisain, Marcel; Mohd Yusoff, Md Sabri; Abdullah, Siti Zahrah (2010)
Bacteria were isolated from the brain, eye and kidney of red tilapia, as well as water and debris samples. The weight and length of red tilapia were measured and the water quality as well. API test were done to identify the type of bacteria from the isolates. In Kenyir Lake, bacterial isolates that predominated in the fish were Micrococcus spp. and Aeromonas hydrophila at 13.64 %, in water samples it was Staphylococcus xylosus at 40% and in the debris samples, Pseudomonas aeruginosa and Enterobacter cloacae at 50%. In the Semantan River, the predominant bacteria in fish and debris samples were Aeromonas hydrophila at 23.53 % and 90 % respectively. In the water samples, Staphylococcus lentus and Staphylococcus xylosus were the predominant bacteria with 30 and 20%, respectively. The ammonia, sulphide, iron and nitrite-nitrogen levels in the Semantan River were over the acceptable limits and this may lead to high fish mortality. This study concluded that Aeromonas hydrophila and Staphylococcus spp. were the most predominant bacteria in red tilapia and poor water quality played a major role in red tilapia succumbing to infections by pathogenic bacteria.